PENERAPAN RESTORATIF TERHADAP PELAKU TINDAK PIDANA KORUPSI KAITANNYA DENGAN PENGEMBALIAN KERUGIAN NEGARA (ANALISIS PUTUSAN PENGADILAN NEGERI PALU NOMOR : 13/Pid.Sus-TPK/2022/PN. Palu) - Moh Albadani Hidayat (Universitas Tadulako, 2025)
This research aims to determine the implementation of restorative measures against perpetrators of criminal acts of corruption in relation to returning state losses by analyzing the decision of the Palu District Court number 13/Pid.Sus-Tpk/2022/PN. Palu. The method used is based on the focus of the study and normative legal research. The results of research on the application of restorative measures to recover state losses in criminal acts of corruption are studied from the perspective of the economic theory of analysis of law, so that the provision of criminal sanctions against perpetrators of criminal acts of corruption will be more effective and efficient in recovering state losses. with the principal criminal charge, and the return of the replacement money in the event of a return to state finances does not mean erasing the principal criminal prosecution.Crime, Court Decisions, and Decision Analysis Peneltian ini bertujuan untuk mengetahui Penerapan Restoratif terhadap pelaku tindak pidana korupsi kaitannya dengan pengembalian kerugian negara dengan analisis putusan pengadilan negeri palu nomor 13/Pid.Sus-Tpk/2022/PN. Palu.Metode yang di gunakan yaitu Berdasarkan fokus kajian dari penelitian hukum normatif. Hasil penelitian penerapan restoratif terhadap pengembalian kerugian negara dalam tindak pidana korupsi dikaji dalam perspektif teori ekenomi analysis of law maka dalam pemberian sanksi pidana terhadap pelaku tindak pidana korupsi akan lebih efektif dan efisian dalam pemulihan kerugian negara.dan Pidana uang pengganti merupakan pidana tambahan yang harus disertai dengan pidana pokok, dan pengembalian uang pengganti tersebut dalam hal pengembalian keuangan negara tidak berarti menghapus tuntutan pidana pokoknya.